Meningkatkan Konsep Diri Akademik Siswa Dengan Teknik Miracle Question Pada Siswa Kelas VIII Di SMP Negeri 2 Sumberrejo - Susilawati, Susilawati (Universitas Nusantara PGRI Kediri, 2020)
One of the elements forming student self-identity in the academic field is the academic self-concept. Some cases of students whose learning outcomes have not been achieved or there is no understanding in certain lessons are due to not understanding their own academic self-concept. Counseling Guidance in Schools as a forum for providing services to students is indispensable in providing counseling services. One of the services provided is group counseling. The techniques provided in group counseling services in this study are the miracle question technique, through this technique students will collaborate with the counselor in group counseling services in finding solutions so that they can make changes to individuals so that they can promote a positive academic self-concept. This study aims to improve students' academic self-concept and use classroom action research with 2 cycles, namely cycles 1 and 2. The results of changes in cycles 1 and 2 are an increase of 10% towards the very high category and 7% of the subjects into the high category.